A review on the Representative Volume Element-based multi-scale simulation of 3D woven high performance thermoset composites manufactured using resin transfer molding process. (June 2023) - Trofimov, Anton; Ravey, Christophe; Droz, Nicolas; Therriault, Daniel; Lévesque, Martin
Abstract: This review shows the potential of using the Representative Volume Element concept for the multi-scale simulation of 3D woven high performance thermoset composites manufactured using the Resin Transfer Molding (RTM) process. Based on the reviewed state of art, this work unleashes the 5 most promising areas for future research that could advance the RTM process optimization. Area 1: Developing polymer constitutive models databases that rely on the experimental data at all ranges of degrees of cure and temperatures involved in the RTM process. Area 2: Verifying the accuracy of simulation tools on complex parts made of different preform types. Area 3: Increasing computational efficiency of degree of cure- and temperature-dependent viscoelastic constitutive models accounting for the stress relaxation. Area 4: Increasing computational efficiency of the multi-scale homogenization procedure. Area 5: Standardizing experimental measurements during different phases of the RTM process.